GADD45B predicts lung squamous cell carcinoma survival and impacts immune infiltration, and T cell exhaustion - Ying Lv; Zeyu Liu; Kai Xiong; Hailing Duan; Jiuyu Yang; Pan Liao (Taylor & Francis Group, 2023)
Background: This study focussed on exploring the prognostic prediction performance of the growth arrest and DNA damage-inducible 45 beta (GADD45B) and its associations with T-cell activity and immune soakage in different malignancies, especially lung squamous cell carcinoma (LUSC). Methods: We applied TIMER database for comparing the expressions of GADD45B among different cancers. OncoLnc, Gene Expression Profiling Interactive Analysis 2 (GEPIA2), and Kaplan-Meier Plotter were utilised to evaluate the prognostic prediction performance of GADD45B. Besides, the associations of GADD45B with clinical stage, associated gene markers, and immune infiltration were examined through TISIDB, GEPIA2, and Tumour Immune Estimation Resource (TIMER). Biological processes (BPs) and KEGG enrichment analyses were performed to illustrate the possible role of GADD45B in LUSC. The miRWalk database was adopted to analyse the gene miRNA interaction network of GADD45B in LUSC. Results: GADD45B expression was decreased in most of the malignancies, with relation to the poor prognosis in LUSC. GADD45B also significantly affected the survival of LUSC subgroups divided by clinic data. GADD45B significantly correlates with and may stimulate T cell exhaustion in LUSC. Conclusions: GADD45B is a prognostic indicator in multiple tumours, especially in LUSC. Moreover, modulating GADD45B expression may improve immunotherapy efficacy in LUSC.